2020
DOI: 10.1038/s41698-020-00129-0
|View full text |Cite
|
Sign up to set email alerts
|

Honeybee venom and melittin suppress growth factor receptor activation in HER2-enriched and triple-negative breast cancer

Abstract: Despite decades of study, the molecular mechanisms and selectivity of the biomolecular components of honeybee (Apis mellifera) venom as anticancer agents remain largely unknown. Here, we demonstrate that honeybee venom and its major component melittin potently induce cell death, particularly in the aggressive triple-negative and HER2-enriched breast cancer subtypes. Honeybee venom and melittin suppress the activation of EGFR and HER2 by interfering with the phosphorylation of these receptors in the plasma memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
101
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(118 citation statements)
references
References 87 publications
(113 reference statements)
4
101
0
2
Order By: Relevance
“…Despite the significantly highest antineoplastic activity showed by FLV-MEL combination, the activity of MEL alone is also worth of mention. In fact, as showed in almost all in vitro cell experiments, the antineoplastic activity of MEL alone used at a sub-toxic concentration (IC10) was higher than that of the free drug (FLV-R) and is in accordance with several recent research studies ( Sangboonruang et al, 2020 ; Yu et al, 2020 ) such as that carried out by Duffy et al showing the ability of MEL to suppress epidermal growth factor receptors 1 and 2 (EGFR and HER2) activation in the aggressive triple-negative and HER2-enriched breast cancer subtypes ( Duffy et al, 2020 ). The present findings also confirm that the combination of this natural product with other antineoplastic drugs results in a more powerful anticancer activity.…”
Section: Discussionsupporting
confidence: 90%
“…Despite the significantly highest antineoplastic activity showed by FLV-MEL combination, the activity of MEL alone is also worth of mention. In fact, as showed in almost all in vitro cell experiments, the antineoplastic activity of MEL alone used at a sub-toxic concentration (IC10) was higher than that of the free drug (FLV-R) and is in accordance with several recent research studies ( Sangboonruang et al, 2020 ; Yu et al, 2020 ) such as that carried out by Duffy et al showing the ability of MEL to suppress epidermal growth factor receptors 1 and 2 (EGFR and HER2) activation in the aggressive triple-negative and HER2-enriched breast cancer subtypes ( Duffy et al, 2020 ). The present findings also confirm that the combination of this natural product with other antineoplastic drugs results in a more powerful anticancer activity.…”
Section: Discussionsupporting
confidence: 90%
“…Melittin is a 26 amino acid residue linear peptide from the honeybee, which kills bacterial cells by permeabilisation of the membrane [ 25 ]. Melittin is also active against eukaryotic parasites such as Leishmania and cancer cells [ 26 ]. The second AMP, pexiganan, also a linear peptide, is the first eukaryotic AMP developed as a drug mainly to treat foot ulcers.…”
Section: Introductionmentioning
confidence: 99%
“…Css 54 exerted antimicrobial activity with low MIC compared to antibiotics against some strains. In a previous study, treatment with melittin showed no adverse effects on stomach tissue, including its function, and melittin was confirmed to have a protective effect against gastric inflammation and antitumor effects in vivo [39][40][41]. These reports indicate that Css54 can be developed as an effective treatment because of its lower toxicity (versus melittin).…”
Section: Discussionmentioning
confidence: 97%